Use of Torulaspora delbrueckii Co-fermentation With Two Saccharomyces cerevisiae Strains With Different Aromatic Characteristic to Improve the Diversity of Red Wine Aroma Profile - Zhang, Bo-Qin; Luan, Yu; Duan, Chang-Qing; Yan, Guo-Liang (Frontiers in Microbiology, 2018)
The use of selected Saccharomyces and non-Saccharomyces strains as mixed starters has advantages over pure fermentation due to achieving wine products with distinctive and diversified aroma expected by consumers. To obtain a way to improve the aroma diversity and increase the differentiation of wine product, in this study, the aromatic effect of multi-culture of indigenous Torulaspora delbrueckii (TD12), simultaneous and sequential inoculation with two Saccharomyces strains (indigenous icewine yeast SC45 and commercial yeast BDX) with different enological characteristics were investigated in laboratory-scale 20 L fermenter, respectively. The results showed that T. delbrueckii co-fermented with different S. cerevisiae strain could generate diversified physicochemical and aromatic quality of wine as evidenced by PCA. Mixed fermentation of SC45/TD12 produced higher contents of higher alcohol (3-methyl-1-pentanol and phenylethyl alcohol), ethyl esters (ethyl decanoate and ethyl butanoate), terpenes and phenylacetaldehyde with less fatty acids (hexanoic acid, octanoic acid) and acetic acid, while BDX/TD12 generated more C6 alcohol (1-hexanol) and acetate esters (ethyl acetate and isoamyl acetate). Compared to simultaneous inoculation, sequential inoculation could achieve higher aroma diversity and generate higher intensity of fruity, flowery and sweet attributes of wine as assessed by calculating the odor activity values. The different S. cerevisiae strain and inoculation method in alcoholic fermentation could further influence the formations of aromatic compounds in malolactic fermentation. Our results highlighted the importance of S. cerevisiae strain in shaping the aromatic quality of wine in mixed fermentation, and also suggested that using different S. cerevisiae strains with distinct aromatic characteristics co-fermentation with specific non-Saccharomyces strain is a potential way to increase the aromatic diversity and quality of wine product, which could provide an alternative way to meet the requirement of wine consumers for diversified aromatic quality.